Macroecological trend of increasing values of intraspecific genetic diversity and population structure from temperate to tropical streams. Issue 8 (18th June 2021) - Salinas‐Ivanenko, Sofia; Múrria, Cesc
Abstract: Aim: Assuming genetic variants are selectively neutral, estimates of intraspecific genetic diversity and population structure should increase simultaneously in parallel to coalescent time, population size and gene flow. However, other processes, such as genetic drift associated with demographic fluctuations, might cause a loss of genetic diversity while not affecting population structure. In this study, we assess large‐scale patterns of estimates of intraspecific genetic variation across species to determine the roles of dispersal, biogeography, divergence time and demographic fluctuations in decoupling genetic diversity and population structure. Location: Pristine first‐order streams distributed in seven regions from Neotropical to boreal climate, covering a gradient of habitat persistence through major biogeographical changes (e.g., Pleistocene glaciations). Time period: 2008–2010. Major taxa studied: Freshwater insect lineages that differ in dispersal propensity. Methods: Intraspecific nucleotide diversity (π) and population structure (ΦST ) were estimated for 33 species using 2, 128 sequences of the cox1 gene. The correlation between π and ΦST was tested using linear regression models. The geographical distribution of haplotypes was represented in networks. Phylogenetic trees were time calibrated to determine divergence time. Results: At a global scale, a positive relationship between π and ΦST was found. Neotropical species showed the highest values of π and ΦST, probably owing to historical environmental stability. Across Europe, the low estimates of π and the wide array of ΦST values and haplotype networks found across species, lineages and latitude were contrary to the biogeographical and dispersal paradigms. Main conclusions: Beyond the macroecological trend found, genetic trajectories of co‐distributed temperate species were disassociated from their functional traits and probably caused by persistent demographic fluctuations associated with local‐scale habitat instability. Overall, the idiosyncratic relationship between π and ΦST across species prevents the establishment of conclusive global patterns and questions the phylogeographical patterns established when studying a reduced number of co‐distributed species.